(untitled) (Research, Society and Development, 2023)
Exogenous intoxication is defined as a pathological process produced by substances that generate an imbalance in the body mediated by biochemical reactions. In the state of Pará, despite the scarcity of data on the epidemiological profile of intoxication, it is known that the use of drugs mainly with suicidal intent and pesticide-induced intoxication are the main agents. The present study aimed to analyze the epidemiological profile of exogenous intoxication cases in the state of Pará between the years 2012 to 2022. This is an epidemiological, descriptive, retrospective and cross-sectional study based on data submitted to the Information System of Notifiable Diseases, and made available through the Department of Informatics of the Unified Health System (DATASUS). The data collected presented information about the type of exposure, toxic agent, age group, gender, and macroregion. The cases notified of exogenous poisoning in the state of Pará corresponded to 6951 between the years 2012 to 2022. In the state of Pará, drugs were also the toxic agent that generated the most exogenous intoxication, corresponding to 28.09%, being more prevalent in the age group of 20 to 39 years. About 82.94% of the intoxications occur at home, and 88.98% are associated with the digestive route. The present study reinforces the need for the adoption of interventionist measures in the state of Pará, encompassing the identification of the types of exposure, health education, measures to prevent recurrence, and encouragement of mental health conservation.